2-Dimensional Pressure Distribution in Saturated Petroleum Reservoir using Finite Difference - Adam Sukma Putra; Wahyu Srigutomo (Institut Teknologi Bandung, 2016)
The aim of this project is to solve the Darcy’s Equation using the finite difference (FD) method. We test the governing equation by investigating a saturated petroleum reservoir in two-dimensional (2-D) system to describe the distribution of the pressure within the reservoir. We assume that the velocity of the fluid (oil) is incompressible and relatively slow as a consequence that the system is saturated. The model used is a flow in steady state 2-D porous media. We apply the modified form of FN method with Gauss-Seidel to improve the precision of the simulation.